2011
DOI: 10.1007/s11661-011-0923-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solute in the Texture Modification During Hot Deformation of Mg-Rare Earth Alloys

Abstract: Although conventional Mg alloys develop strong crystallographic textures during deformation that persist during annealing, the addition of rare earth (RE) elements can induce comparably weaker textures. The texture weakening effect is explored using hot-rolled Mg-Y alloys of a single phase to focus on the possibility of solute effects. Of the studied compositions, the richer alloys ( ‡0.17 at. pct) show the weakening effect, whereas the most dilute alloy (£0.03 at. pct) does not. Electron backscattered diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
170
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 347 publications
(178 citation statements)
references
References 68 publications
(103 reference statements)
8
170
0
Order By: Relevance
“…This observation led to the suggestion that segregation is likely to be important in enabling much higher concentrations than added in the bulk to be achieved locally. [16,17] Once a critical level of RE is achieved, further texture weakening does not occur with more RE addition. [18] It was also shown that the potency of an element in weakening the strong basal texture scales inversely with the solubility of the element; i.e., for elements with a higher solubility, more RE is needed to produce a texture change.…”
Section: Understanding the Rare-earth Effect: Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…This observation led to the suggestion that segregation is likely to be important in enabling much higher concentrations than added in the bulk to be achieved locally. [16,17] Once a critical level of RE is achieved, further texture weakening does not occur with more RE addition. [18] It was also shown that the potency of an element in weakening the strong basal texture scales inversely with the solubility of the element; i.e., for elements with a higher solubility, more RE is needed to produce a texture change.…”
Section: Understanding the Rare-earth Effect: Backgroundmentioning
confidence: 99%
“…This is because as already discussed, the ''RE texture'' only occurs on recrystallization and unrecrystallized grains typically show textures that are very similar to those in non-RE alloys. [8,14,17] An essential characteristic of RE additions in producing the observed texture change is a potent effect on recrystallization. In particular, RE additions can result in inhibition of dynamic recrystallization (DRX) and a change in DRX mechanism.…”
Section: Understanding the Rare-earth Effect: Backgroundmentioning
confidence: 99%
See 3 more Smart Citations